2018
DOI: 10.1021/acs.molpharmaceut.7b01036
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Efficacy of Free and Nanoparticle Formulations of Gallium(III) meso-Tetraphenylporphyrine against Mycobacterium avium and Mycobacterium abscessus and Gallium Biodistribution in Mice

Abstract: The nontuberculous mycobacterial (NTM) pathogens, M. avium complex (MAC) and M. abscessus, can result in severe pulmonary infections. Current antibiotics confront significant challenges for treatment of these NTM infections due to emerging multidrug-resistance. Thus, development of new antibiotics targeted against these agents is needed. We examined the inhibitory activities of Ga(NO), GaCl, gallium meso-tetraphenylporphyrine (GaTP), and gallium nanoparticles (GaNP) against intra- and extracellular M. avium an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 49 publications
3
54
0
Order By: Relevance
“…Our previous works demonstrated that macrophage-targeted Ga(III) nanoparticles have a prolonged antimicrobial effect against Mycobacterium abscessus, Mycobacterium avium, Mycobacterium tuberculosis, and Mycobacterium smegmatis within macrophages because of sustained Ga(III) release over time (27)(28)(29)39). In the current work, we found that THP-1 cells preloaded with GaMP, CDGaPP, or eFGaMP exhibited resistance to P. aeruginosa infection, but only for 3 days, losing all activity at day 5 postloading.…”
Section: Discussionmentioning
confidence: 47%
“…Our previous works demonstrated that macrophage-targeted Ga(III) nanoparticles have a prolonged antimicrobial effect against Mycobacterium abscessus, Mycobacterium avium, Mycobacterium tuberculosis, and Mycobacterium smegmatis within macrophages because of sustained Ga(III) release over time (27)(28)(29)39). In the current work, we found that THP-1 cells preloaded with GaMP, CDGaPP, or eFGaMP exhibited resistance to P. aeruginosa infection, but only for 3 days, losing all activity at day 5 postloading.…”
Section: Discussionmentioning
confidence: 47%
“…We also demonstrated that long-acting Ga nanoparticles (GaNP) inhibited the growth of both HIV and the attenuated H37Ra strain of M. tuberculosis during coinfection within human monocyte-derived macrophages (MDMs) in vitro (1921). Treatment of the HIV-H37Ra coinfected macrophages by GaNP reduced the secretion of IL-6 and IL-8 for up to 15 days.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies done by us and other research groups demonstrated that gallium disrupts iron acquisition by intracellular mycobacteria and Gram-positive and Gram-negative bacteria (11, 15, 16). Macrophage-targeted (mannose-tagged) nanoparticles have been developed to increase drug delivery to macrophages and demonstrated significant growth inhibition of mycobacteria relative to untreated controls (1719). We also demonstrated that long-acting Ga nanoparticles (GaNP) inhibited the growth of both HIV and the attenuated H37Ra strain of M.…”
Section: Introductionmentioning
confidence: 99%
“…As highlighted in Table 3 , intracellular DSTs can differ in selected cell types and experimental procedures. The human monocytic cell lines THP-1 and U937 are commonly used to screen antimicrobial molecules and investigate dose-response against intracellular NTM [ 26 , 27 , 28 , 29 , 30 ]. These cells are differentiated by phorbol 12-myristate 13-acetate (PMA) to mimic the morphology and functions of mature macrophages.…”
Section: Static Intracellular Infection Modelsmentioning
confidence: 99%